1999
DOI: 10.1002/(sici)1097-0142(19990901)86:5<756::aid-cncr9>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the cyclin-dependent kinase inhibitor p21WAF1/CIP1 and p53 tumor suppressor in dysplastic progression and adenocarcinoma in Barrett esophagus

Abstract: BACKGROUND Barrett esophagus predisposes individuals to esophageal carcinoma, which develops from intermediate stages of tissue dysplasia primarily in the vicinity of the gastroesophageal junction. Understanding the cellular and molecular events in the progression of Barrett esophagus to adenocarcinoma may contribute to its early diagnosis and treatment. Mutation and overexpression of the tumor suppressor p53 have previously been observed in Barrett high grade dysplasia and adenocarcinoma. The expression of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 24 publications
0
22
0
2
Order By: Relevance
“…The comparison of the same tumor areas with p53 and p21 expression showed discrepant results in most cases; therefore, it is believed that p21 expression is independent of p53 protein (23) . According to HANAS et al (13) , an overexpression of p21 was observed in a small series of three patients with adenocarcinoma. And to CHATELAIN et al (8) , in another small series, p21 was overexpressed in 2 superfi cial adenocarcinomas, and in most cases, p21 expression was not related to p53 expression.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…The comparison of the same tumor areas with p53 and p21 expression showed discrepant results in most cases; therefore, it is believed that p21 expression is independent of p53 protein (23) . According to HANAS et al (13) , an overexpression of p21 was observed in a small series of three patients with adenocarcinoma. And to CHATELAIN et al (8) , in another small series, p21 was overexpressed in 2 superfi cial adenocarcinomas, and in most cases, p21 expression was not related to p53 expression.…”
Section: Discussionmentioning
confidence: 92%
“…In human cells, p21 is considered a major factor in the up-regulation of the nuclear expression of p53 (10) . p21 has been expressed in several malignant neoplasms, including esophageal adenocarcinomas (8,13,23) . p21 expression also varies considerably in adenocarcinoma and epidermoid carcinoma of the esophagus (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations